2015
DOI: 10.1007/s40806-015-0022-8
|View full text |Cite
|
Sign up to set email alerts
|

Men Ejaculate Larger Volumes of Semen, More Motile Sperm, and More Quickly when Exposed to Images of Novel Women

Abstract: Males in many species differentially allocate sperm and seminal fluid depending on certain social variables, including perceived sperm competition and female reproductive status. In some species, males reduce their investment in sperm quantity or quality upon repeated matings with the same female and increase such investment when mated to a novel female. We tested for effects of stimulus habituation and novelty on ejaculated semen parameters in humans. We analyzed ejaculates produced through masturbation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…In some cases, these changes in sperm motility can occur almost instantaneously. For example, in humans, males produce ejaculates with more motile sperm after viewing stimulus material with competitor males [2] and novel females [3]. A full spermatogenic cycle in humans takes over 70 days [4].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, these changes in sperm motility can occur almost instantaneously. For example, in humans, males produce ejaculates with more motile sperm after viewing stimulus material with competitor males [2] and novel females [3]. A full spermatogenic cycle in humans takes over 70 days [4].…”
Section: Introductionmentioning
confidence: 99%
“…This may explain why the two regression models accounted for a small percentage of the variance: The duration of abstinence is consistently one of the strongest predictors of ejaculate volume (WHO 2010). Indeed, in studies that investigate the strategic adjustments in ejaculate quality, participants are instructed to abstain for at least 48 h prior to submitting their ejaculates for analysis (Joseph et al 2015;Kilgallon and Simmons. 2005;Leivers et al 2014) Future replications of the current research could secure information about the most recent ejaculation prior to each copulation to increase the explanatory power of the models.…”
Section: Discussionmentioning
confidence: 99%
“…For example, men produce ejaculates with greater volume from copulation (i.e., more arousing) than from masturbation (i.e., less arousing; Zavos 1985;Zavos and Goodpasture 1989), and during copulation uninterrupted until ejaculation (i.e., more arousing) than during coitus interruptus (i.e., less arousing; Zavos et al 1994). Men produce higher quality masturbatory ejaculates when they spend more (versus less) time sexually aroused and when they view more (versus less) sexually arousing stimuli (Kilgallon and Simmons 2005;Leivers et al 2014;Joseph et al 2015). Men who report greater sexual arousal report more intense orgasm, more forceful ejaculation , and produce an ejaculate with greater volume (van Rouen et al 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although surpassing a climactic threshold may be a particularly significant experiential event, it is important to keep in mind that sexual acts and orgasms can be qualitatively different and that differences in enjoyment and intensity can modulate the degree of conditioning. In men, these differences may influence ejaculate characteristics in ways that make a given fertilization more likely, possibly even at the expense of near-future fertilization attempts with other potential mates (Joseph, Sharma, Agarwal, & Sirot, 2015; Parker & Pizzari, 2010). In women, it has also been suggested that orgasms could influence the probability of conception (Pavlicev & Wagner, 2016; Puts et al, 2012), although this view is controversial (Levin, 2011); theoretically, more intense or multiple orgasms may have even greater influences on conception probabilities.…”
Section: Surpassing Thresholds: Variable Impacts Of Rhythms and Variamentioning
confidence: 99%